COMPREHENSIVE CREDIT RISK ASSESSMENT OF UKRAINIAN BANKS - Hrytsenko, Larysa; Pavlenko, Liudmyla; Kozhushko, Iryna; Erişen, Onur (Socio-economic relations in the digital society, 2025)
Credit risk is an integral element of banking activities, the identification and effective management of which is essential in today’s environment. The financial stability of both individual banks and the banking sector as a whole depends on the feasibility and effectiveness of risk management. The purpose of the study is to systematise the approaches approved at the state level to assessing the credit risk of banks, analyse the current state of the loan portfolio of the Ukrainian banking sector, and identify the most promising methods of optimising potential risks to its quality. The study examines the essential features of the bank credit risk as well as the most common methods for its assessment. On the basis of a deep analysis of the Resolution of the National Bank of Ukraine No. 351, a detailed algorithm for calculating the amount of bank credit risk is proposed, and its main principles, which are important for the activities of domestic banks, are described. A statistical study of the quality of the loan portfolio of the banking sector of Ukraine for the time horizon of 2018 – 2024 is carried out and a gradual adaptation of the sector’s entities to the unstable conditions of the operating environment is revealed. The results of the analysis also pointed to a deterioration in the level of credit risk coverage of non-performing customer debt in the period 2022 – 2024, which may have negative consequences for the banking sector’s resilience. Based on the results of the study, the possible methods of optimising credit risk have been proposed, which application will have a significant positive effect on the financial stability of the sector and, as a result, the development of the national economy. A promising area for further research is the study of the possibilities of introducing digital tools for monitoring, controlling and preventing the growth of credit risk in banks.